Implementasi Kurikulum Berbasis Cinta melalui Program Infaq Beras dalam Mengembangkan Nilai Empati dan Kepedulian Sosial Anak Usia Dini - Dwi Kasihani; Irmiani; Anna tiana Deli Siregar; Tutut Agus Susanti; Afrida (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The Character education in early childhood requires an approach that is not only conceptual but also grounded in authentic and meaningful direct experience. This study aims to describe the implementation of a love-based curriculum through the Rice Infaq Program at TK Krayan Long Ikis, and to analyze its role in developing empathy and social care values in early childhood. The study employed a descriptive qualitative approach with children aged 4–6 years, teachers, and the school principal as subjects. Data were collected through observation, in-depth interviews, and activity documentation, then analyzed interactively through data reduction, data presentation, and conclusion drawing, with source and technique triangulation to ensure data validity. The findings reveal that the “1 Day 1 Liter of Rice Movement” and “Blessed Friday” programs effectively develop children’s empathy and social care through three key mechanisms: direct interaction with beneficiaries, consistent and repeated prosocial habituation, and integration of Islamic philanthropic values into daily life. The novelty of this research lies in the integration of a love-based curriculum with structured philanthropic practices involving synergy among school, family, and community, thereby forming stable, authentic, and sustainable character dispositions in early childhood.